THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN INSTRUCTING RELIGIOUS VALUE - Ahmad Hariandi; Brigita Novianti Butar-butar; Endang Juliana; Puput Wulandari; Tati Karyati (STAI Hubbulwathan Duri, 2020)
This research aims to identify the role of Islamic religion teachers in instilling religious values in elementary schools. Data collecting is done by making direct observations of intensive learning activities and learning outside which are considered to prioritize attitude or religious. The research method used is a qualitative descriptive approach. This type of research is a phenomenological research. This research examines a phenomenon that exists in SD Negeri 182/1 Lindung Hutan. The result of this research shows that the role of Islamic religious education teachers is very important in instilling religious values in schools. The teacher is a model in the process of instilling religious value for the students.